0806 Prescription Correlates of Nightmare Disorder Among Veterans. (27th May 2020) - Gross, M; Patel, R; Schwartz, S W; Sebastião, Y V; Foulis, P; Scheer, D; Taylor, K A; Anderson, W
Abstract: Introduction: In the James A. Haley Veterans Administration (JAHVA) Vista database, the ICD-9 code 307.47 for Nightmare disorder (ND) is infrequently used and appears independently of codes for PTSD. We wanted to determine if certain drugs that may affect sleep are associated with ND. Methods: All patients with ND visiting JAHVA between 2007 and 2011 were selected along with control patients who visited JAHVA on one of 20 random days, one day each quarter year. Controls were assigned an index date reflecting their selection quarter. Associations with prescriptions for opioids, antidepressants (SSRI's, SSNI's, Tricyclics), antihistamines and benzodiazepine/Z-drugs were initially investigated. Two analyses were performed: risk factor analysis- patients with ND diagnosis dates (cases) or index dates (controls) prior to 2008 were excluded and only prescription dates that preceded the ND diagnosis or index date were considered; treatment analysis- cases and controls with a ND diagnosis date or index date after 2010 were excluded and only prescription dates that were subsequent to the ND diagnosis or index date respectively were considered. Logistic regression adjusting for age, gender, race and Hispanic ethnicity was used to determine the association between drug groups and ND. Results: In risk factor analysis (667 cases, 14, 739 controls), opioids and antihistamines were significantly less prevalent among would-be ND patients than controls (OR=0.627 and 0.610 respectively); no drug group was predictive of ND. In contrast, all drug groups were significantly associated with ND in treatment analysis (803 cases, 15, 530 controls). The strongest associations were seen with benzodiazepine (OR=3.026; 95% CI: 2.472, 3.703) and SSRI (OR=2.789; 95% CI=2.316, 3.358) prescriptions. Conclusion: Our data suggest that some JAHVA providers may be treating ND with medication, most notably with benzodiazepines/Z-drugs and antidepressants. The role of anti-histamine and opioid prescriptions needs further elucidation. The ramifications of these treatment decisions should be explored. Support: This material is the result of work supported with resources and the use of facilities at the James A. Haley Veterans' Hospital.